2016
DOI: 10.4034/pboci.2016.161.22
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Oral Hygiene Level and Periodontal Condition in Brazilian Adolescents

Abstract: Objective: To evaluate the oral hygiene level and periodontal condition of adolescents aged 15-19 years and socioeconomic factors. Material and Methods: Cross-sectional study with 630 adolescents from public schools randomly selected in the city of Campina Grande, Brazil. For data collection, a form containing socioeconomic variables and those related to oral hygiene was used. The oral hygiene level was measured through the Simplified Oral Hygiene Index (OHI-S) and periodontal condition was evaluated by the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Brazilian adolescents, the prevalence of healthiness was only 1.6%, and gingival bleeding and presence of calculus were the most frequent changes, 34.4% and 37.8%, respectively [12].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Brazilian adolescents, the prevalence of healthiness was only 1.6%, and gingival bleeding and presence of calculus were the most frequent changes, 34.4% and 37.8%, respectively [12].…”
Section: Discussionmentioning
confidence: 95%
“…Epidemiological surveys are essential for the surveillance of oral diseases such as periodontal diseases through the diagnosis of these diseases, it is possible to guide decision making in the implementation of effective preventive and curative policies, so that adolescents can reach adulthood with periodontal health [12].…”
Section: Discussionmentioning
confidence: 99%
“…The regular brushing teeth twice a day decrease dental caries. Previous research has shown that 59.7% of adolescents were satisfactory with level of the oral hygiene [21]. A significant correlation has been observed between teeth brushing times (>2 minutes: 47.0% of respondents) and dental caries activity [22].…”
Section: Discussionmentioning
confidence: 99%
“…The term periodontal disease includes inflammatory conditions of infectious origin, located at the level of the supporting tissues of the tooth, the periodontium [1,2], the inflammatory component results from a microbial aggression modulated by the response of the host.…”
Section: Introductionmentioning
confidence: 99%